Feeding Behavior as Affected by Diverse Physical Forms of Complete Feed in Indigenous Gir Cattle of Semi-Arid Region of India - Kumawat, Manish; Sharma, Vishnu; Karnani, Monika; Sharma, Sanjita (Indian Journal of Animal Nutrition, 2017)
This study was aimed to assess the effect of diverse physical forms of complete feed on feed intake and feeding behavior in indigenous Gir cattle of semi-arid region of India. A feeding trial of 60 days duration was carried out on twelve lactating Gir cattle divided into 3 groups of 4 animals in a randomized block design. The animals were fed 3 iso-nitrogenous diets containing complete feed mash, complete feed pellet and complete feed block in groups CFM, CFP and CFB, respectively. Densification of complete diets increased the bulkdensity by 3.1-3.9 times. The effect of diverse physical forms of complete feed on feeding behavior showed significant differences (P